2019
DOI: 10.1038/s41598-019-43899-9
|View full text |Cite
|
Sign up to set email alerts
|

Th1, Th17, and Treg Responses are Differently Modulated by TNF-α Inhibitors and Methotrexate in Psoriasis Patients

Abstract: Psoriasis is a chronic, recurrent, immune-mediated, hyperproliferative inflammatory skin disease. The role of the adaptive immune system, particularly of Th1 and Th17 lymphocytes, has been regarded as prominent in the immunopathogenesis of psoriasis, as well as decreased Tregs function. Immunobiological drugs were administered in therapeutic pulses and a few studies evaluate their effects on the immune repertoire. The aim of this study was to evaluate the adaptive immune profile of patients with severe psorias… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
59
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(64 citation statements)
references
References 57 publications
2
59
2
1
Order By: Relevance
“…Previous studies reported that Th1 and Th17 cells have critical roles in the pathogenesis of psoriasis [16]. Inflammatory cytokines, including IL-17, IFN-γ, and TNFα, are also involved in the inflammatory process of psoriasis [17]. Taken together, the pathogenesis of psoriasis involves complicated immune regulation with Th1 and Th17 dysregulation.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Previous studies reported that Th1 and Th17 cells have critical roles in the pathogenesis of psoriasis [16]. Inflammatory cytokines, including IL-17, IFN-γ, and TNFα, are also involved in the inflammatory process of psoriasis [17]. Taken together, the pathogenesis of psoriasis involves complicated immune regulation with Th1 and Th17 dysregulation.…”
Section: Discussionmentioning
confidence: 98%
“…It was previously demonstrated that TNF-α antagonists have high efficacy for the treatment of psoriasis by inhibiting the inflammation cascade triggered by TNF-α [25]. Studies also reported that anti-TNF therapy interfered with immune responses to modulate the productions of IFN-γ, TNF-α, and IL-17A [17]. However, the exact mechanisms involved in the effects of pathogenic cytokines in psoriasis and antipsoriatic treatment with TNF-α antagonists remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from therapeutics with a direct effect on IL-17 family members, there is accumulating evidence for a reduction of lesional IL-17 levels with known systemic drugs for plaque psoriasis including methotrexate (Furiati et al, 2019;Reich et al, 2019a).…”
Section: Current Therapies Targeting Il-17 Cytokinesmentioning
confidence: 99%
“…Higher serum concentration of FABP5 in our study may re ect its epidermal level. The underlying mechanism of the association of FABP5 and psoriasis is not clear yet, but one of the possible explanation is role of the adaptive immune system, particularly of Th1 and Th17 lymphocytes, which has been regarded as prominent in the immunopathogenesis of psoriasis [19]. Interestingly, studies have shown that FABP5 can increase Th17-cell differentiation [20] and aberrant FABP5 activity may over activate immune cells leading to in ammatory autoimmune diseases [21].…”
Section: Discussionmentioning
confidence: 99%